Sex differences in symptom severity, cognition and psychosocial functioning among individuals with at‐risk mental state for psychosis. Issue 1 (16th February 2021) - Chan, Kwun Nam; Chang, Wing Chung; Ng, Chung Mun; Lee, Hoi Ching; Chan, Suet In; Chiu, San Yin; Wong, Cheuk Fei; Wo, Sui Fung; Lee, Ho Ming; Chan, Kit Wa; Wong, Ming Cheuk; Chan, Kwok Ling; et al.
Abstract: Aim: Sex differences are well documented in schizophrenia, but have been much less studied in at‐risk mental state (ARMS) for psychosis. We aimed to examine sex differences in symptomatology, cognition, social and role functioning in individuals with ARMS, with specific focus on clarifying relationships between sex, negative symptoms and functioning. Methods: One hundred and seventy‐seven Chinese participants aged 15–40 years with ARMS were recruited from a specialized early intervention service in Hong Kong. ARMS status was verified by Comprehensive Assessment of At‐Risk Mental State. Assessments encompassing symptom profiles, a brief battery of cognitive tests and social and role functioning were conducted. Brief Negative Symptom Scale was adapted to measure negative symptoms at the level of five core domains. Results: Males with ARMS exhibited significantly poorer social functioning and more severe asociality of negative symptoms than female counterparts. Mediation analysis revealed that sex difference in social functioning became statistically insignificant when asocality was included in the model, indicating that asociality mediated the relationship between sex and social functioning. No sex differences were observed in other core domains of negative symptoms, other symptom dimensions, cognitive measures and role functioning. Conclusions: This study suggests that sex differences in ARMS may be less pronounced that those observed in established psychotic disorders. Our findings of differential pattern of asociality between sexes and its mediating role on sex difference in social functioning underscore the importance in investigating negative symptoms at a separable domain‐level. Further research is required to identify sex‐specific predictors of longitudinal outcomes in at‐risk populations.